2020
DOI: 10.3390/agronomy10020211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonchemical Protection of Broad Bean on Epigeic and Soil Arthropodofauna—Analysis in Field-Realistic Conditions

Abstract: Plant protection methods, even those considered as safe for the environment and consumers, may have unexpected effects on nontarget organisms. The effect of broad bean protection, using Pythium oligandrum, paraffin-coated garlic pulp, and extract from grapefruit seeds and pulp on the abundance of epigeic and soil arthropodofauna in a 3-year field experiment was estimated. The effect was compared with chemical protection, which served as the reference to the conventional system. Use of nonchemical products did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, other studies showed that coriander as a companion plant had no significant effect on the number of root nodules produced by broad beans [95]; the fruit fresh weight and proportions of marketable fruit of strawberries [90]; or the total number of fruits, the number of marketable fruits, the total fruit yield, or the marketable yield of tomatoes [102] when compared to monoculture. Intercropping coriander with broad beans resulted in a lower yield of broad beans (708.46 kg/ha).…”
Section: Impacts On Growth Parameters and Yield Of Cropsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, other studies showed that coriander as a companion plant had no significant effect on the number of root nodules produced by broad beans [95]; the fruit fresh weight and proportions of marketable fruit of strawberries [90]; or the total number of fruits, the number of marketable fruits, the total fruit yield, or the marketable yield of tomatoes [102] when compared to monoculture. Intercropping coriander with broad beans resulted in a lower yield of broad beans (708.46 kg/ha).…”
Section: Impacts On Growth Parameters and Yield Of Cropsmentioning
confidence: 94%
“…Coriander as an intercrop in broad bean affected the feeding of pea leaf weevils, Sitona spp. (Coleoptera: Curculionidae), on broad bean [95]. spp.…”
Section: Influence On Pestsmentioning
confidence: 99%
“…1,25,[32][33][34][35][36][37][38][39] Secondary damage can result from root rot pathogens that can infect insect-damaged tissue. 40,41 In the absence of management intervention, yield loss has been estimated to be as much as 2114 kg per acre. 18 Producers have relied on pesticides to manage PLW, with applications of insecticide to the seed prior to planting and one or two foliar sprays targeting the adults in the spring season.…”
Section: Introductionmentioning
confidence: 99%
“…The species is distributed in Albania (Guéorguiev, 2007), Lithuania (Tamutis et al 2011), Estonia (Ploomi et al 2003), Germany (Frеudе et al 2004), the Netherlands (Turin et al 1977), Serbia (Popović and Štrbac 2010) and throughout Ukraine (Kryshtal 1956;Putchkov 2011Putchkov , 2018Brygadyrenko 2015a;Putchkov et al 2020) and Moldova (Karpova and Matalin 1993;Nekuliseanu and Matalin 2000). Kryzhanovskij et al (1995) provided a detailed characteristic of species in the territory of the former Soviet Union: the Urals, the middle stretch of West Siberia, South of West Siberia, the plains of Kazakhstan, the plains of Central Asia, and a part of Transcaucasia, Tian-Shan, mountains of South-East part of Central Asia, the Altais-Sayan Mountains, Transbaikalia, Cisamuria and the Maritime Provinces.…”
Section: Introductionmentioning
confidence: 99%